JNK Signaling Pathway Mediates Acetaminophen-Induced Hepatotoxicity Accompanied by Changes of Glutathione S-Transferase A1 Content and Expression - Chenxi Shi; Beili Hao; Yang Yang; Ishfaq Muhammad; Yuanyuan Zhang; Yicong Chang; Ying Li; Changwen Li; Rui Li; Rui Li; Fangping Liu; Fangping Liu (Frontiers in Pharmacology, 2019)
Acetaminophen (APAP) is an analgesic–antipyretic drug and widely used in clinics. Its overdose may cause serious liver damage. Here, we examined the mechanistic role of c-Jun N-terminal kinase (JNK) signaling pathway in liver injury induced by different doses of APAP. Male mice were treated with APAP (150 and 175 mg·kg−1), and meanwhile JNK inhibitor SP600125 was used to interfere APAP-induced liver damage. The results showed that JNK signaling pathway was activated by APAP in a dose-dependent manner. C-Jun N-terminal kinase inhibitor decreased JNK and c-Jun activation significantly (P < 0.01) at 175 mg·kg−1 APAP dose, and phosphorylation levels of upstream proteins of JNK were also decreased markedly (P < 0.05). In addition, serum aminotransferases activities and hepatic oxidative stress increased in a dose-dependent manner with APAP treatment, but the levels of aminotransferases and oxidative stress decreased in mice treated with JNK inhibitor, which implied that JNK inhibition ameliorated APAP-induced liver damage. It was observed that apoptosis was increased in APAP-induced liver injury, and SP600125 can attenuate apoptosis through the inhibition of JNK phosphorylation. Meanwhile, glutathione S-transferases A1 (GSTA1) content in serum was enhanced, while GSTA1 content and expression in liver reduced significantly with administration of APAP (150 and 175 mg·kg−1). After inhibiting JNK, GSTA1 content in serum decreased significantly (P < 0.01); meanwhile, GSTA1 content and expression in liver enhanced. These findings suggested that JNK signaling pathway mediated APAP-induced hepatic injury, which was accompanied by varying GSTA1 content and expression in liver and serum.